The education of ethnic minorities in Beijing - Hasmath, R (2011)
This article investigates the operations of minority schools, and the subsequent on-the-ground experiences of ethnic minorities in Beijing at the primary, secondary and tertiary levels. The article suggests that the 'inter-sectionality' of ethnic identities, particularly minority-majority, rich-poor and urban-rural, must be factored in when examining the varying differences between minorities who have graduated from Beijing's minority schools and non-Beijing ethnic minorities, who have enrolled in the capital city's universities. The article draws upon recent statistical data, interviews with minority actors and public stakeholders, and participant observation in the city's schools and universities. © 2011 Copyright Taylor and Francis Group, LLC.